The aptness of antagonistic protocol in intracytoplasmic sperm injection: Embryologic study - Sharef, Tuqa Yousif (Zanco Journal of Medical Sciences (ZJMS), 2019)
Background and objective: Infertility and poor ovarian response are serious problems in our society; fortunately the in vitro fertilization and intracytoplasmic sperm injection technique dissolve many of these problems. This study aimed to assess the effect of an individualized GnRH antagonist regimen on intracytoplasmic sperm injection process especially the aptness of it in given mature reiterative oocytes, normal fertilization, and acceptably zygote cleavage which enhance pregnancy. Methods: The population of the study consisted of 877 couples attending the in vitro fertilization-infertility center in the maternity teaching hospital and chose to undergo intracytoplasmic sperm injection after using of antagonist protocol for stimulation of women ovaries. The women ages ranged between 24 and 44 years. The collected data included a number of reiterative oocytes; fertilization, embryo grades and lastly estimates the pregnancy results Results: A significant association (P <0.001) was found in the numbers of reiterative oocytes between the age groups of the study. A significant association (P = 0.005) was also found concerning to quality of fertilization process. The study of the zygote cleavage and blastomeres formation followed the fertilization show variable grade of embryos and analyzed data of embryo grades in this study indicate presence of significant association (P = 0.003). The rate of pregnancy showed significant association between the groups of the study with the <30 years age group have chance of pregnancy higher than other groups. Conclusion: The antagonist protocol of ovary stimulation according to the results of this study is a qualified protocol; besides it is rapid and can be reversed. This protocol can give effective results in the intracytoplasmic sperm injection process especially for young women, and enhance the pregnancy.